ALASAN MASUK DAN ALASAN MEMILIH PROGRAM STUDI ANTARA ALUMNI DI UNIVERSITAS TERBUKA - Sri Listyarini; Tina Ratnawati; Prayekti Prayekti; Milwan Milwan (LPPM Universitas Terbuka, 2012)
Universitas Terbuka (UT) as an open and distance higher education institution needs to have data on the student reasons why they enrolling at UT and why they choose their study programs. The data can be obtained from alumni who recently graduated, for that UT has developed an exit survey applications. There are two programs that are managed by UT, the Regular Program or Non-Pendas and Basic Education Program (Pendas). In this study respondents of the exit survey consist of 3,190 Regular Program alumni and 34,856 Program Pendas alumni, which is a graduate of UT during 2009.2 to 2010.2 semesters. The results of exit survey data processing shows that there are some differences regarding the reasons for the UT enrollment and reasons for choosing study program, among the Regular and Pendas Program alumni. The main reason for the Regular and Pendas Program alumni enrolled at UT is